An Analysis of Grammatical Errors Committed by the Tenth Grade Students of SMA Negeri 1 Baturiti in Writing Recount Text in Academic Year 2014/2015 - Purnayatri, L A; Seken, I Ketut; Adnyani, L D.S. (Lingua Scientia, 2016)
The present study aimed at 1) finding the types of grammatical errors committed by the tenth grade students of SMA Negeri 1 Baturiti in writing recount text in academic year 2014/2015; and 2) finding the sources of the errors committed by the tenth grade students of SMA Negeri 1 Baturiti in writing recount text in academic year 2014/2015. This study was designed as descriptive-qualitative study. The methods used to collectdata were document analysis and interview. The instruments used were project and interview guide. The data in this study were analyzed by using data analysis theory proposed by Miles and Hubarman. The types of grammatical errors used in this study were based on the surface strategy taxonomy proposed by Dulayat alwhile the sources of the errors were based on the combination of theories proposed by Richards and Brown. Model of error analysis used in this study was the one proposed by Gass and Selinker. The result of the study showed that the subject committed 167 errors in their writing, namely misformation (29.94%), addition (27.54%), omission (24.55%), and misordering (17.96%).